Hubungan Antara Konsep Diri Dengan Kecanduan Game Online Pada Pemain Game Mmorpg - Pandu Dwi Pamungkas; Sayang Ajeng Mardhiyah; Maya Puspasari (Universitas Muhammadiyah Jember, 2019)
This aim of study was to examine the relationship between self-concept and game online MMORPG player. Whereas the hypothesis proposed in this study is there was at relationship with self-concept and game online addiction in game MMORPG. The sample of this study was 100 gamers who was game MMORPG. The questioner used was game online addiction scale and self-concept scale. The sample used purposive sampling technique in order to get the sample. The result of the study was analyzed by pearson product momen technique. The result of the study showed that there was a negative significant relationship between self-concept and game online addcition in player game MMORP with value r = -0,393 and p = 0,000 (p0,05). Therefore, the hypothesis is accepted. Keywords : Self-Concept, Game Online Addiction